ACCOUNTING STUDENTS' PERCEPTIONS OF TAX EVASION: RELIGIOSITY AS A POTENTIAL FACTOR - Erawati, Teguh; Harun, Silvana (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This investigation examines the influence of religiosity, tax knowledge, and tax fairness on accounting students' perceptions of tax evasion. Grounded in the Theory of Planned Behavior (TPB), this research addresses the critical role of future accountants as ethical gatekeepers. A quantitative explanatory design was employed, involving 90 accounting students from Universitas Sarjanawiyata Tamansiswa (2019–2022 cohorts) selected via purposive sampling. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The findings demonstrate that religiosity and tax knowledge significantly and negatively influence perceptions of tax evasion, indicating that strong spiritual anchors and cognitive proficiency enhance ethical rejection of fraudulent practices. Conversely, tax fairness was found to have a significant positive effect on perceptions of tax evasion. This